If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n=5(n-4)2+2n
We move all terms to the left:
n-(5(n-4)2+2n)=0
We calculate terms in parentheses: -(5(n-4)2+2n), so:We get rid of parentheses
5(n-4)2+2n
We add all the numbers together, and all the variables
2n+5(n-4)2
We multiply parentheses
2n+10n-40
We add all the numbers together, and all the variables
12n-40
Back to the equation:
-(12n-40)
n-12n+40=0
We add all the numbers together, and all the variables
-11n+40=0
We move all terms containing n to the left, all other terms to the right
-11n=-40
n=-40/-11
n=3+7/11
| 2x+20°=3x+10° | | 2/3x-7=0 | | 1/4x-3=x+4 | | 29-x=27 | | 16g=784 | | m²–9m+20=0 | | 4x-6=2(x-3)=8 | | v/11=26 | | 6(2x+3)-4=38 | | h12=-6 | | 7(t+2)+4t=2t+-4 | | 28=y/28 | | g+115=180 | | y=1;2y-1+7 | | -72=-18k | | 25b=125 | | 48=(6x+6) | | 6b=966 | | 2x-7-3x=6-(x+3) | | (6x+4)=38 | | 8(3x-1)-4=4x+2 | | h/22=5 | | 14=x10 | | 4/12=11/p | | -23m=207 | | y+1.6=8.56 | | 7y-20=90 | | 4/12=11p | | 14x-4+3x+6-1x=-30 | | j/20=27 | | -8(3x–6)=6(4x+8) | | 6b-8=-28 |